The motivation for engineering change in the industrial company - Maceika, Augustinas; Toločka, Eligijus (Business: Theory and Practice, 2021)
The authors of this article established the goal to investigate parameters related to the staff motivation for engineering change in the industrial company as case study and to predict the ways of improving the performance of the company. Employees of the company can be more motivated to generate innovative ideas and to implement them. That can be related to the better engineering change situation. For this reason, in this work, we have explored the environment and opportunities to improve the engineering performance of the company in the context of engineering change. The authors of the paper have conducted several studies, collected and analysed important information. Methods used – review of scientific literature and other sources of information, case study, structural systematic analysis, and sociological survey of industrial company personnel based on hypothesis. The object of the research was motives for engineering change in the industrial company. Motivated organizational behaviour actions, that focus on creation and realization of innovative ideas for engineering change, can be based on creation of an innovation-friendly environment. As our research has shown, it is important to consider parameters related to the staff motivation, such as, satisfaction with the company’s declared policy, satisfaction with the management’s behaviour in encouraging employees, freedom of employees to communicate and take creative initiative.